FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN LABA (STUDI KASUS PADA PT. KAPUAS PERMATA MEDIFARMA PONTIANAK) - Jaurino (Jurnal Akuntansi, Auditing dan Investasi, 2021)
The purpose of the study was to determine whether credit sales, accounts receivable turnover and bad debts had a partial or simultaneous effect on operating profit. The research method uses quantitative methods, or statistical analysis with 36 samples obtained from the monthly financial statements of PT. Kapuas Permata Medifarma for three periods, from 2018 - 2020. The research variables used are the independent variables (Credit Sales, Accounts Receivable Turnover and Uncollectible Accounts) and the Dependent Variable (Operating Profit). Hypothesis testing using multiple linear regression with t test and F test and correlation test. The results showed that partially credit sales had a significant effect on operating profit, while the turnover of receivables and bad debts had no significant effect on operating income. Simultaneously credit sales, accounts receivable turnover and bad debts have an effect on operating profit. When viewed from the level of correlation that credit sales have a very strong relationship with profit, while the turnover of receivables and bad debts has a low relationship with profit. Keywords: Credit Sales, Accounts Receivable Turnover, Doubtful Accounts and operating profit